2019
DOI: 10.1038/s41598-019-43261-z
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-related receptor alpha induces epithelial-mesenchymal transition through cancer-stromal interactions in endometrial cancer

Abstract: Estrogen-related receptor alpha (ERRα), which shares structural similarities with estrogen receptors, is associated with tumor progression in endometrial cancer, but little is known about the detailed underlying mechanism. We investigated whether ERRα, in cooperation with peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), could participate in epithelial-mesenchymal transition (EMT) in endometrial cancer through cancer-stromal interactions. Two endometrial cancer cell lines, Ishikawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…First, our results demonstrated that different concentrations of estrogen had different effects on normal endometrial epithelial cells, and relatively high doses of estrogen (30 nM) inhibited cell proliferation by promoting the progress of EMT in normal endometrium. Previous studies found that estrogen was sensitive to EMT progression in endometrial cancer and endometriosis ( 24 , 25 ). Since endometrial fibrosis is the main cause of IUA occurrence and poor prognosis, we further investigated the impact of the same dose of estrogen on EMT in the fibrotic environment.…”
Section: Discussionmentioning
confidence: 90%
“…First, our results demonstrated that different concentrations of estrogen had different effects on normal endometrial epithelial cells, and relatively high doses of estrogen (30 nM) inhibited cell proliferation by promoting the progress of EMT in normal endometrium. Previous studies found that estrogen was sensitive to EMT progression in endometrial cancer and endometriosis ( 24 , 25 ). Since endometrial fibrosis is the main cause of IUA occurrence and poor prognosis, we further investigated the impact of the same dose of estrogen on EMT in the fibrotic environment.…”
Section: Discussionmentioning
confidence: 90%
“…Some of these findings are reminiscent of results reported in breast cancer (BC), where ER down-regulates E-cadherin levels and fosters EMT process [65,66]. It is noteworthy that recent studies also reported a role for the nuclear orphan estrogen-related receptor alpha (ERR) in EMT and progression of lung [67] as well as endometrial [68] cancer cells.…”
Section: Estrogen Receptor (Er) α In Epithelial Mesenchymal Transimentioning
confidence: 85%
“…In this regard, several studies have shown that Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), mammalian target of rapamycin (mTOR), and c-Myc pathways regulate biogenesis and mitochondrial activity in metastatic cells. These pathways are able to suppress the expression of E-cadherin, to stimulate the expression of epithelial–mesenchymal-transition-associated factors, such as vimentin and Snail, and also to positively regulate the Transforming Growth Factor-β1 (TGF-β1)-Induced EMT [ 21 , 22 , 23 , 24 ].…”
Section: Mitochondria and Cancermentioning
confidence: 99%